2022
DOI: 10.3390/jcm11133718
|View full text |Cite
|
Sign up to set email alerts
|

Stool Elastase as an Independent Prognostic Factor in Patients with Pancreatic Head Cancer

Abstract: (1) Background: Patients with pancreatic exocrine insufficiency (PEI) have an increased risk of malnutrition, which in turn increases morbidity and mortality and is frequent in pancreatic head cancer. This study aimed to analyze the utility of PEI measured using the stool elastase (SE) level to predict the prognosis of patients with pancreatic head cancer. (2) Methods: Patients who underwent pancreaticoduodenectomy for pancreatic cancer at our institution between 2011 and 2015 were included. Only patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
(35 reference statements)
0
1
0
Order By: Relevance
“…In patients with pancreatic adenocarcinoma, a factor contributing to malnutrition is pancreatic exocrine insufficiency (PEI). Exploring the impact of PEI in patients with pancreatic cancer undergoing curative surgery, Hwang et al recently identified a prognostic value of stool elastase (SE), a marker to detect PEI, in patients with pancreatic head cancer who have undergone pancreaticoduodenectomy [ 2 ]. Overall survival (OS) and disease-free survival (DFS) were significantly shorter in the low-SE group, while SE levels remained a significant predictor of OS and DFS in the multivariable analysis.…”
mentioning
confidence: 99%
“…In patients with pancreatic adenocarcinoma, a factor contributing to malnutrition is pancreatic exocrine insufficiency (PEI). Exploring the impact of PEI in patients with pancreatic cancer undergoing curative surgery, Hwang et al recently identified a prognostic value of stool elastase (SE), a marker to detect PEI, in patients with pancreatic head cancer who have undergone pancreaticoduodenectomy [ 2 ]. Overall survival (OS) and disease-free survival (DFS) were significantly shorter in the low-SE group, while SE levels remained a significant predictor of OS and DFS in the multivariable analysis.…”
mentioning
confidence: 99%